A Sustainable Rehabilitation Model for Children in Conflict with the Law: Conceptually Toward Global Protection and Recidivism Reduction - Nur, Rafika; Darmawati, Darmawati; Lahaling, Hijrah; Bakhtiar, Handar Subhandi; Mohammed Zabidi, Ahmad Fakhrurrazi (Jambura Law Review, 2026)
This study employs a Research and Development methodology, guided by the ADDIE framework, to design a sustainable restorative digital rehabilitation model for children in conflict with the law. It responds to critical systemic deficiencies observed in juvenile justice, including fragmented service delivery, non standardized intervention protocols, and persistently high recidivism rates. Data were synthesized from structured literature reviews, field observations at LPKA Class II Gorontalo, expert consultations, and controlled pilot trials. The principal outputs comprise a detailed process architecture, operational workflow maps, and a modular integrated application. This digital platform consolidates standardized assessment, intervention tracking, behavioural monitoring, and post-release reintegration support. Validation analyses indicate that the proposed model adheres to normative child justice standards and demonstrates technical feasibility for scalable implementation. The framework enhances intervention precision, improves the measurement of behavioural transformation, and strengthens readiness for community reintegration. Consequently, this research contributes a hybrid socio-legal and digital framework designed to increase systemic reliability and standardisation in juvenile rehabilitation. The model presents a scalable solution with potential global relevance for reducing recidivism among young offenders.